Standards of basic dataset of chronic and noncommunicable diseases behavior risk factor surveillance in adults (T/CPMA 033 - 2023) - Chinese Preventive Medicine Association (Editorial Office of Chinese Journal of Public Health, 2024)
Standards of basic dataset of chronic and noncommunicable diseases behavior risk factors surveillance in adults (T/CPMA 033 - 2023) was published and formally implemented by Chinese Preventive Medicine Association on October 20th, 2023. The standard stipulates the metadata attributes and data element attributes of the adult chronic noncommunicable disease behavioral risk factors monitoring dataset. It is suitable for related data collection of monitoring, investigation, intervention and evaluation of behavioral risk factors of chronic and noncommunicable diseases developed by health administrative departments, disease prevention and control institutions, primary-level medical and health care institutions, health examination and management institutions and scientific research institutes.